An NDT guided wave technique for the identification of corrosion defects at support locations. (October 2015) - Andruschak, Nicholas; Saletes, Izella; Filleter, Tobin; Sinclair, Anthony
Abstract: Due to the large number of pipe supports over a piping run, a rapid reliable NDT system is needed to identify hidden corrosion defects at a pipe-support interface. To accomplish this, a system using Periodic Permanent Magnet (PPM) Electromagnetic Acoustic Transducers (EMAT׳s) to generate dispersive SH1 guided waves is implemented. For this study, both the effect of the support contact and a corrosion type defect are evaluated independently through finite element models and experiments utilizing a flat plate approximation. It was found that utilizing the SH1 plate wave near the inflection point or 'knee' of the dispersion curve yields a high sensitivity to gradual wall loss defects while experiencing a minimal effect from the support contact. Highlights: A rapid screening technique for defects detection at pipe-support interfaces is presented. Axially orientated PPM EMAT's are used to generate SH1 guided waves. Support contact and defect effects are evaluated through FE models and experiments. The technique is insensitive to support contact, but has a high defect sensitivity.